Polyamines in tomato plants grown during an incidence of tospovirus exposure - Guimares, Leysimar R. P. [UNESP]; Soler, Julia M. P.; Lima, Giuseppina P. P. [UNESP]; Pavan, Marcelo A. [UNESP] (Springer, 2014)
This study aimed to evaluate the effect of an agrochemical mixture, Pyraclostrobin + Metiram (Cabrio Top)A (R) (P + M), and Bacillus subtilis on polyamine levels and their potential relationship with plant growth stages. These experiments were conducted in an area of historical disease occurrence. Thirty-two hundred tomato plants (cv. "Saladinha Plus") were used. The trays were divided into two groups; one group received a pre-treatment of P + M (3 g l (-1)) and Boscalid A (R) (0.3 g l (-1)), and no products were applied to the other half of the tray. After transplanting, the following spray treatments were used: P + M (2.0 g l (-1)), P + M (4.0 g l (-1)), B. subtilis (4.0 ml l (-1)) and MethamidophosA (R) (1.0 ml l (-1)) for 20, 35, 50 and 65 days after (DAT). To analyze the free polyamine concentrations (putrescine, spermidine and spermine), the plant material was collected at 30, 45, 60, and 75 DAT. The fruit harvest and the assessment of the total production and average fruit weight were performed at 80 DAT by selecting 20 plants from each treatment group. Higher concentrations of putrescine and spermidine were found in the plants exposed to P + M at 4.0 g l (-1), indicating that polyamine concentrations may be correlated with the plant's resistance to stress. The optimal production and weight of the tomatoes were obtained following the application of P + M, demonstrating that this agrochemical mixture has great potential to protect tomato crop yields when applied during periods of high disease incidence.
Keywords: Free polyamines; Solanum lycopersicum; Phenology; Agrochemical; Virus